LEGAL CERTAINTY AND AGRARIAN JUSTICE REGARDING THE POLICY OF ERASING WRITTEN EVIDENCE OF LAND FORMERLY CUSTOMARY - Virdy Varlucy Watdi; Gunawan Djayaputra (RADJA PUBLIKA, 2025)
The policy of eliminating written proof of ownership for former customary land, such as Girik, Petok D, Letter C, and Ketitir, as specified in Government Regulation Number 18 of 2021, has various implications for legal certainty and agrarian justice. This study aims to analyze the impact of this policy on the land ownership status of customary communities and small-scale farmers. The research employs a normative juridical method with a legislative and case study approach. The findings indicate that this policy may increase legal uncertainty for landowners without certificates, complicate the process of proving land rights, and potentially exacerbate agrarian inequality. To address these issues, solutions such as accelerating free land registration, enhancing public awareness, and strengthening the role of local governments and customary institutions in facilitating land ownership legalization are needed. With a more inclusive and equitable approach, this policy can be implemented without ignoring the rights of customary communities while remaining aligned with the principles of agrarian justice and legal certainty.